2010
DOI: 10.1057/hsq.2010.14
|View full text |Cite
|
Sign up to set email alerts
|

Trends in social inequalities in male mortality, 2001–08. Intercensal estimates for England and Wales

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
2
8
0
1
Order By: Relevance
“…It would be necessary to observe another period with a substantial relative improvement in life expectancy for the Routine class before there could be confidence that a turning point had been reached for inequalities in male mortality. The relative improvement in the Routine class for men was consistent with the findings of Langford and Johnson (2010), using a cross-sectional method with the Labour Force Survey forming the basis for population denominators. This suggested that mortality rates at working age for Routine class males fell by the most of any of the NS-SEC analytic classes between 2001 and 2008.…”
Section: Discussionsupporting
confidence: 81%
“…It would be necessary to observe another period with a substantial relative improvement in life expectancy for the Routine class before there could be confidence that a turning point had been reached for inequalities in male mortality. The relative improvement in the Routine class for men was consistent with the findings of Langford and Johnson (2010), using a cross-sectional method with the Labour Force Survey forming the basis for population denominators. This suggested that mortality rates at working age for Routine class males fell by the most of any of the NS-SEC analytic classes between 2001 and 2008.…”
Section: Discussionsupporting
confidence: 81%
“…Occupations are differentiated in terms of reward mechanisms, promotion prospects, autonomy and job security. The most advantaged NS‐SEC classes (higher managerial and professional) typically exhibit personalised reward structures, have good opportunities for advancement, relatively high levels of autonomy within the job, and are relatively secure (these attributes tending to be reversed for the most disadvantaged, or routine, class) (Langford and Johnson 2010).…”
Section: Class Socioeconomic Classifications (Secs) Health and Longmentioning
confidence: 99%
“…A study of male mortality between 2001 and 2008, for example, found that in 2001 the mortality rate of those in routine and manual occupation was 2.0 times that of those in managerial and professional occupations; in 2008 that ratio had risen to 2.3. The authors note that ‘this pattern of declining absolute but rising relative inequalities is a well‐known phenomenon in the context of declining overall mortality rates’ (Langford and Johnson 2010: 1). The recent Strategic Review of Health Inequalities (The Marmot Review 2010) affords comprehensive coverage of SECs and health and longevity.…”
Section: Class Socioeconomic Classifications (Secs) Health and Longmentioning
confidence: 99%
“…While comparison with the results for men is complicated by the enforced omission of the age group 60-64, (where naturally a higher rate of mortality occurs than between 25 and 59), the results show some major differences to those obtained for men (Langford and Johnson, 2010).…”
Section: Comparison With the Results For Menmentioning
confidence: 61%
“…While there were statistically significant differences between the two sets of results for certain NS-SEC classes, the overall pattern and the scale of inequality were very similar. Following this, a recent article (Langford and Johnson 2010) used LFS based population data to provide annual denominators by age and occupation in order to estimate male mortality rates by NS-SEC for each year between 2001 and 2008.…”
Section: Introductionmentioning
confidence: 99%